Ground state ferromagnetism in a generalized Hubbard model with strong correlations - Didukh, L.; Kramar, O. (Condensed Matter Physics, 2003)
The present paper considers the ground state ferromagnetic ordering in
a generalized Hubbard model with correlated hopping and interatomic exchange
interaction in the case of strong correlations at non-integer band
filling. The quasi-particle energy spectrum is obtained by means of a generalized
mean-field approximation. The ground state energy of the system
and the condition of ferromagnetic state realization are calculated. The dependences
of magnetization on energy parameters and band-filling are obtained. В роботі розглядається основний феромагнітний стан для узагальненої моделі Габбарда з корельованим переносом та міжатомною обмінною взаємодією у випадку сильних електронних кореляцій та нецілого заповнення зони. З використанням узагальненого наближення середнього поля отримано квазічастинковий енергетичний спектр. Розраховано енергію основного стану та умову реалізації феромагнітного впорядкування. Отримано залежності намагніченості системи від значень енергетичних параметрів моделі та заповнення зони.